(untitled) (International Journal of Current Engineering and Technology, 2015)
Company Mindarika had reported poor quality of particular products in the Assembly department which results in increasing cost, lead time, and customer complaints. The purpose of this study is to help Company Mindarika to improve the product quality and to manage the data for a continuous improvement plan by using Continuous Process Improvement and the Quality Control Techniques. Methods and procedures of this study include a review of literature relevant to Continuous Improvement, Quality Control Techniques, Root cause Analysis, Seven Tools of Quality and Assembly process of a specific automotive product (Lever Combination Switch). After the causes of defects were identified, solutions and procedures were recommended to the Company to eliminate defects in the assembly process of Lever Combination Switch.